An evaluation of the normal range of StO2 measurements at rest and following a mixed exercise protocol. Issue 4 (28th August 2014) - Barker, Tom; Spencer, P; Kirkman, E; Lambert, A; Midwinter, M
Abstract : Background: Assessment of local tissue oxygenation (StO2 ) using near infrared spectroscopy is an emerging technique in medical practice with applications in trauma/sepsis management, diagnosis of acute compartment syndrome and assessment of tissue viability. Despite this, there have been little published data on the range of StO2 values in normal subjects. Methods: StO2 measurements were recorded in 105 infantry soldiers using an INVOS System Monitor (Somanetics) from both deltoids, the anterior compartment of the leg and the frontal lobe of the brain. Measurements were taken at rest and following completion of a mixed exercise protocol, consisting of overarm pull-ups, sit-ups and a 3-mile run. Results: StO2 values at rest were found to have a wide normal range with a skew left distribution. Mean StO2 was similar between the deltoids (left deltoid 80%, right deltoid 79%), but significantly different between other anatomical sites (leg 68%, brain 73%). However, all sites demonstrated a similar lower range cut-off at approximately 40%. Following exercise, there was a significant increase in StO2 values at all sites (left deltoid by 3.1±2.0%, right deltoid by 2.6±2.3%, leg by 8.0±2.3% and brain by 8.6±1.9%), which persisted for at least 10 min. Conclusions: There were statistically significant differences in mean StO2 values recorded at different anatomical sites, although the reference ranges were wide and substantially overlapped. StO2 increased at all sites after exercise with the effect persisting for at least 10 min. The interaction between exercise and pathological phenomena remains unknown and is an area for further study.